Ukrainian Preventive Restructuring : First Transposition of Directive (EU) 2019/1023 by a Non-Member State - Kononov, Oleksiy (European Insolvency and Restructuring Journal, 2024)
Having been granted candidate status for EU membership, Ukraine must transpose Directive (EU) 2019/1023 into its national law. Furthermore, the transposition of the Directive is an explicit requirement for the EU's micro-financial aid to Ukraine. Ukraine faces a rather unique situation, being obligated to reform its insolvency legislation in line with the Directive during a time of war and within tight deadlines set by the EU. Currently, two bills have been filed with Parliament aimed at revising the 2018 Code on Bankruptcy Procedures in accordance with the Directive. The proposed modernizations aim to address the existing problems that Ukrainian businesses face when attempting pre-trial insolvency prevention measures and could prove extremely useful for Ukraine's post-war economic recovery.